KESESUAIAN PERTIMBANGAN HUKUM HAKIM TERHADAP TINDAK PIDANA NARKOTIKA DENGAN SEMA NOMOR 3 TAHUN 2015 - Yohanes Galih Lintario; Hanuring Ayu Ardhani Putri (Verstek, 2023)
Abstract: This article analyzes the suitability of judges' considerations with SEMA Nomor 3 of 2015 inimposing criminal penalties for narcotics crimes. This study aims to find out whether the judge's legalconsiderations in imposing a sentence on Decision Nomor: 3557 K/Pid.Sus/2021 are in accordance withSEMA Nomor 3 of 2015. This research is a normative legal research that is prescriptive and applied. Thelegal material collection technique used in this study is the document study technique or library studytechnique. The collection of legal materials is carried out through document studies and literature studies.Based on the results of the study, it was shown that the basis for legal considerations was that the judgemade a decision in the form of convicting the defendant based on juridical and non-juridical considerationsin accordance with the facts revealed in the trial. The judge's considerations in imposing a criminal decisionagainst the Defendant are in accordance with SEMA Nomor 3 of 2015.Keywords: Narcotics; Narcotics Crime; Judge's Legal Considerations